2002
DOI: 10.3171/jns.2002.97.6.1271
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of cerebrospinal fluid production in patients with chronic hydrocephalus

Abstract: The authors postulate that chronic increased intracranial pressure causes downregulation of CSF production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 25 publications
3
56
1
1
Order By: Relevance
“…Human CSF is renewed three to four times daily (Silverberg et al 2002). Flow of CSF is from lateral ventricles to the third and then through the narrow mesencephalic aqueduct into the fourth ventricle.…”
Section: Ventricular Cerebrospinal Fluidmentioning
confidence: 99%
“…Human CSF is renewed three to four times daily (Silverberg et al 2002). Flow of CSF is from lateral ventricles to the third and then through the narrow mesencephalic aqueduct into the fourth ventricle.…”
Section: Ventricular Cerebrospinal Fluidmentioning
confidence: 99%
“…CSF production has been shown to be relatively constant and unaffected by acute changes in cerebrospinal fluid pressure (CSFP), however, certain drugs (e.g., diuretics, cardiac glycosides and β-blockers), chronic elevation of CSFP and aging can effect CSF production [26,33,34]. With advancing age, flattening and loss of the choroidal secretory epithelium, thickening of the basement membrane, cyst formation, lipid accumulation, fibrosis and calcification, as well as hyalinization and amyloid deposition in choroidal blood vessels is seen [35][36][37].…”
Section: Csf Productionmentioning
confidence: 99%
“…These include: The authors found a significant decrease in CSF production among AD patients and those with NPH, when compared with controls (0.42 ± 0.13 ml/min) and with patients with acute hydrocephalus (0.40 ± 0.13 ml/min). Mean CSF production in AD was 0.20 ± 0.06 ml/min, and in NPH was 0.25 ± 0.08 ml/min (FIGURE 2) [4,34].…”
Section: Measurements Of Csf Production and Turnovermentioning
confidence: 99%
“…The cerebrospinal fluid has a measured normal flow rate of 0.410 ml/min [17,18]. The cerebrospinal fluid both in the brain and in the spinal column form a connected column of liquid.…”
Section: Brain-blood Barrier and Fluid Movementmentioning
confidence: 99%